Mentoring sebagai Sarana Pembelajaran: Studi Kualitatif tentang Efektivitas Program Mentoring dalam Pengembangan Karyawan Pabrik Kasur Desa Tulungagung - Silviana Hastika Dewi; Mudji Kuswinarno (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Mentoring has proven to be successful in developing employees in various industries, such as mattress-making companies in Tulungagung Village. The extent to which mentoring can improve employee skills and performance in the mattress-making industry is the subject of this qualitative research. Research on mattress making was conducted through in-depth interviews with employees involved in the mentoring program. To find patterns and themes that emerged in their experiences, a qualitative approach was used to analyze the data collected. The results showed that the mentoring program had a significant positive effect on employee growth. Employees indicated an increase in their understanding of the mattress manufacturing process, more efficient work techniques, and better interpersonal skills. They also said that they feel more confident and motivated to do new things.